Job stress among Royal Malaysian Police (RMP) personnel - Mohd Hafiz, Mohd Noor (2017)
Stress has been regarded as a major issue in relations to law enforcement officers including police officers. This research aim’s to explore the relationships between various factors and potential sources referred to as “Job Stressor” with job stress among Royal Malaysian Police (RMP) personnel. In this regard, this research attempts to investigate the contribution of workloads, working conditions, role conflict, role ambiguity and workplace relationships factor which is known as primary work-related job stressors towards the relationships with job stress among Royal Malaysian Police (RMP) personnel. This quantitative study was conducted at Royal Malaysian Police and the populations were the police officers stationed at Shah Alam District Police Headquarters (IPD Shah Alam). Data were collected and gathered using survey method and questionnaires are used as the survey instruments. A total of 223 questionnaires were distributed whereby only 181 questionnaires were successfully retrieved. The findings of this study resulted in acceptance on some of the hypotheses formulated for this study. The research findings indicated that workloads and poor supervisory support have positive and significant relationships with the police officers job stress whereas working conditions, role conflict, role expectation, role clarity and interpersonal relationships was found to have no significant relationships with job stress. Hence, the findings of this study contributes to the limited existing literature on policing occupational work stress and also had to some degree, added to the comprehension of understandings and enrich the knowledge regarding policing job stress and job stressor within the landscape of Malaysian policing.